Decoherence Induced by the Environment for Dimerized Anisotropic XY Spin Chain (Journal of Atomic and Molecular Sciences, 2021)
The Loschmidt echo of single qubit coupling to the environment for dimerizedanisotropic XY spin chain in transverse field have been analyzed. We have obtainedanalytical expression for the Loschmidt echo. By numerically computing theLoschmidt echo, we find that the decay of coherence will be enhanced with the increasingof the staggered parameter.